PROBLEMATIKA ASESMEN PEMBELAJARAN PAI BERBASIS MULTIKULTURAL - Rohmah, Putri Ainur; Islah, Ahmad Nur (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
ABSTRACT This study aims to deeply uncover the problematic implementation of assessments in multicultural-based Islamic Religious Education (PAI) learning at SDN Daseh, while also analyzing the causal factors and offering alternative solutions. The background of this study is based on the fact that PAI assessments still predominantly assess cognitive aspects, such as memorization and understanding of teaching materials, while affective and social aspects such as tolerance, empathy, and appreciation for diversity have not received serious attention. This condition has implications for the limited role of assessment in supporting the formation of inclusive student character and able to live harmoniously in a pluralistic society. This study adopted a descriptive qualitative method with data collection through in-depth interviews, observations, and document analysis. The findings of this study indicate that PAI teachers experience difficulties in developing assessment measurement tools that consider multicultural aspects, and there is a lack of adequate training or technical guidance. The assessment rubric does not clearly include multicultural indicators, and the existing assessment process does not reflect the values of diversity that should be in accordance with the school's vision that emphasizes the value of diversity. The conclusion of this study emphasizes the importance of reconstructing Islamic Religious Education (PAI) assessments through the development of relevant, contextual, and holistic indicators and assessment instruments, which encompass cognitive, affective, and social aspects in a balanced manner. This effort is expected to make assessments a tool for developing tolerant, inclusive, and socially just character in students. ABSTRAK Penelitian ini bertujuan untuk mengungkap secara mendalam probematika pelaksanaan asesmen dalam pembelajaran Pendidikan Agama Islam (PAI) berbasis multiultural di SDN Daseh, sealigus menganalisis faktor penybabnya dan menawarkan alternatif solusi. Latar belakang penelitian ini didasarkan pada kenyataan bahwa asesmen PAI masih dominan menilai aspek kognitif, seperti hafalan dan pemahaman materi ajar, sementara aspek afektif dan social seperti toleransi, empati, dan penghargaan terhadap keberagaman belum mendapat perhatian serius. Kondisi ini berimplikasi pada terbatasnya peran asesmen dalam mendukung pembentukan karakter peserta didik yang inklusif dan mampu hidup harmonis di tengah masyarakat majemuk. Penelitian ini mengadopsi metode kualitatif deskriptif dengan pengumpulan data melalui wawancara mendalam, pengamatan, dan analisis dokumen. Temuan dari studi ini mengindikasikan bahwa pengajar PAI mengalami kesulitan dalam menyusun alat ukur asesmen yang mempertimbangkan aspek multikultural, serta belum adanya pelatihan atau panduan teknis yang memadai. Rubrik penilaian tidak secara jelas mencakup indikator multikultural, dan proses asesmen yang ada belum mencerminkan nilai-nilai keberagaman yang seharusnya sesuai dengan visi sekolah yang menekankan nilai kebhinekaan. Kesimpulan dari penelitian ini menekankan pentingnya melakukan rekonstruksi dalam asesmen PAI melalui pengembangan indikator dan instrumen penilaian yang relevan, kontekstual, dan holistik, yang mencakup aspek kognitif, afektif, dan social secara seimbang. Upaya ini diharapkan mampu menjadikan asesmen sebagai sarana pembentukan karakter toleran, inklusif, dan berkeadilan social pada peserta didik.